Perception and awareness of healthcare professionals toward the applications of artificial intelligence in Egyptian healthcare settings - Azzam, Shimaa; El-Morsy, El-Morsy Ahmed; Said, Amira S. A.; Eissa, Nermin; Khalil, Doaa Mahmoud (Frontiers in Artificial Intelligence, 2026)
BackgroundHealthcare professionals’ awareness and handling of artificial intelligence applications in healthcare enhance patient outcomes and improve processes. This study aimed to evaluate the perception, attitude, knowledge, and practice of healthcare professionals regarding the application of artificial intelligence in Egyptian healthcare settings.MethodA cross-sectional study in which 367 healthcare professionals responded to an electronic questionnaire.ResultsOut of 367 participants (234 female), radiology and lab test specialty (36.2%) was the predominant. The mean age was 27.03 years; 51.8% of respondents showed positive perception, 68.7% experienced sub-optimal knowledge, 52.9% expressed negative attitudes, and 53.4% demonstrated a low practice level of AI tools. Younger age was significantly associated with positive perception (adjusted odds ratio (AOR) = 0.905, p = 0.020) and higher AI practice (AOR = 0.907, p = 0.026). University hospital professionals had 61.4% lower odds of optimal knowledge than private hospital professionals (AOR = 0.386, p = 0.046). Men had higher odds of both positive attitudes (AOR = 1.844, p = 0.010) and high practice level (AOR = 2.92, p < 0.001). Pre-bachelor’s holders had lower odds of positive attitudes (AOR = 0.361, p = 0.036), as well as physicians compared to nurses and others (AOR = 0.424, p = 0.005). Bachelor’s holders showed lower odds of high AI practice (AOR = 0.388, p = 0.017).ConclusionDespite moderate perception, most professionals have knowledge, attitude, and practice defects. Mainly, younger age and men showed higher engagement, indicating a need for targeted AI training, especially for older and female professionals.